Chemical and geochemical modeling. Thermodynamic models for binary fluoride systems from low to very high concentration (> 35 m) at 298.15 K - Donchev, Stanislav; Tsenov, Tsvetan V.; Christov, Christomir (Acta Scientifica Naturalis, 2021)
In this study we developed well validated thermodynamic models for solution behavior and solid-liquid equilibrium for all fluoride binary systems, for which activity data are available. The subject of modeling study are 5 fluoride systems of the type 1-1 (HF-H O, NaF-H O, KF-H O, RbF-H O, and CsF-H O) and one of 1-2 type (H SiF -H O) from low to very high concentration at 298.15 K. Models are developed on the basis of Pitzer ion interactions approach. The recommendations on mean activity coefficients (γ ) have been used to construct the model for HF-H O system. To parameterize models for all other 5 binary systems we used all available raw experimental osmotic coefficients data (φ) for whole concentration range of solutions, and up to saturation point. The predictions of new developed here models are in excellent agreement with experimental osmotic coefficients data, and with recommendations on activity coefficients in binary solutions from low to very high concentration: up to 20 mol. kg in HF-H O, and up to 35.6 mol.kg in CsF-H O. The Deliquescence Relative Humidity (DRH (%)) and thermodynamic solubility products (as ln K ) of 4 solid phases [NaF(s), KF.2H O(s), RbF(s), and CsF(s)] have been determined on the basis of evaluated model parameters and using experimental m(sat) solubility data.